On common fixed points of weakly commuting mappings and set-valued mappings - S. Sessa; B. Fisher (International Journal of Mathematics and Mathematical Sciences)
Our main theorem establishes the uniqueness of the common fixed point of two set-valued mappings and of two single-valued mappings defined on a complete metric space, under a contractive condition and a weak commutativity concept. This improves a theorem of the second author.